Effect of a multifactorial interdisciplinary intervention on mobility-related disability in frail older people: randomised controlled trial - Fairhall Nicola (BMC Medicine, 2012)
Abstract Background Interventions that enhance mobility in frail older people are needed to maintain health and independence, yet definitive evidence of effective interventions is lacking. Our objective was to assess the impact of a multifactorial intervention on mobility-related disability in frail older people. Methods We conducted a randomised, controlled trial with 241 frail community-dwelling older people in Sydney, Australia. Participants were classified as frail using the Cardiovascular Health Study definition, did not have severe cognitive impairment and were recently discharged from an aged care and rehabilitation service. The experimental group received a 12 month multifactorial, interdisciplinary intervention targeting identified frailty components. Two physiotherapists delivered a home exercise program targeting mobility, and coordinated management of psychological and medical conditions with other health professionals. The control group received usual care. Disability in the mobility domain was measured at baseline and at 3 and 12 months using the International Classification of Functioning, Disability and Health framework. Participation (involvement in life situations) was assessed using the Life Space Assessment and the Goal Attainment Scale. Activity (execution of mobility tasks) was measured using the 4-metre walk and self-report measures. Results The mean age of participants was 83.3 years (SD: 5.9 years). Of the participants recruited, 216 (90%) were followed-up at 12 months. At this time point, the intervention group had significantly better scores than the control group on the Goal Attainment Scale (odds ratio 2.1; 95% confidence interval (CI) 1.3 to 3.3, P = 0.004) and Life Space Assessment (4.68 points, 95% CI 1.4 to 9.9, P = 0.005). There was no difference between groups on the global measure of participation or satisfaction with ability to get out of the house. At the activity level, the intervention group walked 0.05 m/s faster over 4 m (95% CI 0.0004 to 0.1, P = 0.048) than the control group, and scored higher on the Activity Measure for Post Acute Care (P < 0.001). Conclusions The intervention reduced mobility-related disability in frail older people. The benefit was evident at both the participation and activity levels of mobility-related disability. Trial registration Australia and New Zealand Clinical Trials Register (ANZCTR): ANZCTRN12608000507381.